2012
DOI: 10.1038/aps.2012.35
|View full text |Cite
|
Sign up to set email alerts
|

β-Asarone protects PC12 cells against OGD/R-induced injury via attenuating Beclin-1-dependent autophagy

Abstract: Aim: To explore the effects of β-asarone from Acorus Tatarinowii Schott on autophagy in an ischemic stroke model of PC12 cells. Methods: The ischemic stroke model of PC12 cells was made by OGD/R (2 h oxygen-glucose deprivation followed by 24 h reperfusion). Drug administration was started 1 h before OGD and last for 3 h. Then the cells were incubated in the drug-free and full culture medium under normoxic conditions for 24 h. After the treatments, Beclin-1, intracellular free calcium concentration ([Ca 2+ ] i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…In addition, we found that up‐expression of Beclin‐1‐dependent autophagy protected against β‐amyloid‐induced cell injury in PC12 cells . Also, β‐asarone protects PC12 cells against oxygen‐glucose deprivation and reperfusion‐induced injury by attenuating Beclin‐1‐dependent autophagy . A previous report from our group showed that β‐asarone attenuated ischemia‐reperfusion‐induced autophagy in rat brains by modulating c‐Jun N‐terminal kinase (JNK), phosphorylation of JNK, B‐cell lymphoma 2, and Beclin‐1 .…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, we found that up‐expression of Beclin‐1‐dependent autophagy protected against β‐amyloid‐induced cell injury in PC12 cells . Also, β‐asarone protects PC12 cells against oxygen‐glucose deprivation and reperfusion‐induced injury by attenuating Beclin‐1‐dependent autophagy . A previous report from our group showed that β‐asarone attenuated ischemia‐reperfusion‐induced autophagy in rat brains by modulating c‐Jun N‐terminal kinase (JNK), phosphorylation of JNK, B‐cell lymphoma 2, and Beclin‐1 .…”
Section: Introductionmentioning
confidence: 70%
“…To further clarify the effect of β‐asarone and l ‐dopa co‐administration on autophagy, we employed trasmission electron microscopy, the standard method to detect autophagy . Coronal sections (50–150 μ m) were cut with a vibratome (UC7; Leica EM, Solms, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were treated with OGD/R exposure as previously described [14]. Briefly, balanced salt solution was adopted to wash cells twice, which were then subjected to OGD medium without glucose (in mM: NaCl 116, CaCl 2 0.9, MgSO 4 0.8, KCl 5.4, NaH 2 PO 4 1, phenol red 110, pH 7.4).…”
Section: Oxygen Glucose Deprivation/reoxygenation (Ogd/r)mentioning
confidence: 99%
“… The characteristic ultrastructural morphology of autophagosome (Mo et al, 2012) ( A ) Normal morphology was observed in cytoplasm of the normal control group. Autophagosomes can be hardly observed in this group.…”
Section: Resultsmentioning
confidence: 99%